Since `3x` contains the variable to solve for, move it to the left-hand side of the equation by subtracting `3x` from both sides. `7x+6-3x=-2` Since `7x` and `-3x` are like terms, add `-3x` to `7x` to get `4x` . `4x+6=-2 ` Since `6` does not contain the variable to...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Since `3x` contains the variable to solve for, move it to the left-hand side of the equation by subtracting `3x` from both sides.

`7x+6-3x=-2`

Since `7x` and `-3x` are like terms, add `-3x` to `7x` to get `4x` .

`4x+6=-2 `

Since `6` does not contain the variable to solve for, move it to the right-hand side of the equation by subtracting `6` from both sides.

`4x=-6-2 `

Subtract `2` from `-6` to get `-8` .

`4x=-8 `

Divide each term in the equation by `4` .

`(4x)/4 = -8/4`

Simplify the left-hand side of the equation by canceling the common factors.

`x=-8/4`

Simplify the equation.

`x=-2`

Solve `7x + 6 = 3x - 2`

First move all "x's" to one side by subtracting 3x from each side.

`7x + 6 -3x = 3x-3x-2` `<br>`

`4x+6 = -2`

Now move 6 to the right side by subtracting 6 from each side.

`4x+6-6 = -2-6`

`4x=-8`

Divide both sides by 4 to get "x" alone.

`(4x)/4 = (-8)/4`

` ``x = -2`

**The solution is x = -2.**

``